Punishing tax offenders in France and Great Britain: two criminal policies. Issue 4 (2nd October 2017) - Weidenfeld, Katia; Spire, Alexis
Abstract : Purpose: Since 2008-2009, the governments in France and Great Britain have encouraged more rigorous penalization of tax evaders. This paper aims to investigate the implementation of these policies on the basis of an important and original empirical material. Design/methodology/approach: The study done in France relies on interviews conducted with representatives of law enforcement agencies on public statistics and on an innovative database compiled from nearly 600 cases submitted to the judiciary. The comparison with Great Britain is developed through interviews conducted with different participants in the fight against tax fraud and statistical information. Findings: This paper describes the recent evolution of the machinery for screening tax-related wrongdoings in France and in the UK. It demonstrates that whilst publicly calling for harsh punishment against tax dodgers, in practice, both governments tend to seek a balance between the growing demand for tax equality and the belief that the State should not intervene in the economic realm. This strategy leads to the over-representation of certain categories of taxpayers. Despite the commonalities resulting from the numerous filters before prosecution, the penal strategy takes on two different shapes on either side of the Channel: whereas the British institutions support an "exemplary punitive" system, French regulatory system favours a "quasi-administrative" treatment. The French tax authority continues to use the criminal procedures mainly as a financial instrument for the improved restitution of stolen taxes. The policy of Her Majesty's Revenue and Customs, supported by the "Sentencing Guidelines", aims much more at obtaining exemplary convictions. Originality/value: Based on a large empirical material, this paper highlights the different outcomes of the criminal trials against tax evaders in the two countries.